(Ne)prilagojeni (ZRC SAZU, Založba ZRC, 2022)
The volume (‘(Un)adapted’) contains twenty-one chapters dealing with natural disasters. The chapters describe various research findings and examples of the use of modern technologies in cases of natural disasters. The volume covers various topics such as earthquakes, floods, avalanches, droughts, GIS support, and web applications.